2004
DOI: 10.1177/000312240406900206
|View full text |Cite
|
Sign up to set email alerts
|

Privatizing the Welfare State: Nonprofit Community-Based Organizations as Political Actors

Abstract: S ociological research on public social provision generally is built upon studies of income transfers from governments to individuals. This research has provided valuable information about how income transfer policies are established, why particular categories of people are made eligible, how levels of cash benefits are set, and why eligibility and generosity change over time. Cross-national research has tested theories about why different nations make different policy choices in these areas and what the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
263
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(285 citation statements)
references
References 56 publications
4
263
0
7
Order By: Relevance
“…Although growth-machine politics and the influence of wealthy corporations continue to influence economic development, episodes such as the collapse of the multibillion dollar plan for the 2024 Boston Olympics in the face of widespread public opposition-in considerable part over environmental concernsreveal the increasing importance of civic engagement and grassroots opposition in the politics of urban planning. In addition, the devolution of federal resources in the last few decades has resulted in a sharp move away from direct transfers (e.g., welfare payments to individuals) toward nonprofit organizations serving as mediators of federal support to low-income populations (27,28), reshaping the form of local urban governance. New research in Boston, for example, has also found that community-based organizations superseded elected politicians as the legitimate representatives of the city's economic and infrastructure development of a large corridor running through poor minority neighborhoods (29).…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…Although growth-machine politics and the influence of wealthy corporations continue to influence economic development, episodes such as the collapse of the multibillion dollar plan for the 2024 Boston Olympics in the face of widespread public opposition-in considerable part over environmental concernsreveal the increasing importance of civic engagement and grassroots opposition in the politics of urban planning. In addition, the devolution of federal resources in the last few decades has resulted in a sharp move away from direct transfers (e.g., welfare payments to individuals) toward nonprofit organizations serving as mediators of federal support to low-income populations (27,28), reshaping the form of local urban governance. New research in Boston, for example, has also found that community-based organizations superseded elected politicians as the legitimate representatives of the city's economic and infrastructure development of a large corridor running through poor minority neighborhoods (29).…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…Our hypothesis that blended forms of social action constitute an increasing form of collective civic action in the United States is further motivated by the fact that community-based nonprofit organizations have grown over time and have become increasingly embedded in the political process through the mediation of publicly funded services (Marwell 2004). An intriguing body of research also suggests the potential of local nonprofit organizations to foster collective action (Small 2004;Warren 2004) and to correct for market or government "failures" in the production of public goods (Hansmann 1987;Weisbrod 1988;Berry 2003).…”
Section: Emergence Of Blended Forms Of Actionmentioning
confidence: 99%
“…These appropriately named "hybrid organizations" (Minkoff 2002) are involved with most types of charitable services. Marwell (2004), for example, noted the rise of "machine politics" community based organizations (CBOs), which distribute community services and create reliable voting blocs to elect officials who support the group's mission. Smith and Lipsky (1993) similarly discussed "upstart" organizations, which develop from the contracting out of social service delivery by governments and then play an active role in advocating for the continued and increased funding of programs.…”
Section: The Great Lobbying Dividementioning
confidence: 99%